Japonisme and the Birth of Cinema - Miyao, Daisuke (Book collections on Project MUSE., 2020)
"JAPONISME AND THE BIRTH OF CINEMA explores the influence and impact of traditional Japanese art on the development of early cinematic visual style, particularly with regards to the actuality films created by the French brothers Auguste and Louis Lumiere between 1895 and 1905. Japonisme, a term coined in 1872, has historically been used to broadly describe Japanese influence on French art; in this book, film and media scholar Daisuke Miyao argues that Japonisme goes beyond French imitations of Japanese art to describe the actual application of Japanese principles, methods, and aesthetics in the production of French art. Examining the nearly 1,500 films made by the Lumiere brothers, Miyao argues that far from being insignificant films that sought to capture everyday life, these short films provided a space for experimenting with aesthetic and cinematic styles imported from Japan. Furthermore, Miyao analyzes a set of Lumiere films produced in Japan, and investigates how these films document a negotiation between French Orientalism and Japanese aesthetics. What emerges for Miyao is thus a refutation of Japonisme as merely Orientalism: whereas Orientalism implies a one-directional gaze from West to East that transformed the "Orient" into a static, ahistorical, entity, Miyao argues that Japonisme entailed a multipronged, in-depth engagement with the methods, principles, aesthetic sensibilities, and techniques of Japanese artists that ultimately constituted a two-way conversation between East and West. Chapter 1 argues for a reframing of the Lumiere films as part of a media ecology of photography, painting, and cinema influenced by Japanese compositional and aesthetic styles. In chapter 2, Miyao focuses on the thirty-three Lumiere films produced in Japan, and how the Orientalism of the films was contested by the incorporation of the ukiyo-e-style and engagement with Japanese people. Chapter 3 attends to Japanese reactions to Japonisme through the medium of Japanese filmmaking at the end of the 19th century. This book will be of interest to students and scholars of film and media studies, media archaeology, art history, aesthetics, East Asian studies, and French studies"--